Correction: Mokoena et al. Conjugation of Hypericin to Gold Nanoparticles for Enhancement of Photodynamic Therapy in MCF-7 Breast Cancer Cells. Pharmaceutics 2022, 14, 2212 - Dimakatso Mokoena; Blassan P. George; Heidi Abrahamse (Pharmaceutics)
In the original publication [...]